Sociology of education - Boronski, Tomas; Hassan, Nasima (SAGE, 2015)
This textbook explains the basic principles of sociology and relates these concepts to today's society and education system in order to deepen your understanding of how these issues affect our lives and the world we live in, encouraging you to think critically and to develop a 'sociological imagination'.